2015
DOI: 10.1093/cid/civ098
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Inoculation of the Commensal Neisseria lactamica Inhibits Carriage of Neisseria meningitidis by Young Adults: A Controlled Human Infection Study

Abstract: NCT02249598.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
91
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 27 publications
2
91
0
3
Order By: Relevance
“…This is most likely because N . lactamica works as a protective agent against meningococcal colonization either by stimulating immune response from the host or by competing for the same ecological niche [40]. …”
Section: Discussionmentioning
confidence: 99%
“…This is most likely because N . lactamica works as a protective agent against meningococcal colonization either by stimulating immune response from the host or by competing for the same ecological niche [40]. …”
Section: Discussionmentioning
confidence: 99%
“…Given that pathogenic and commensal Neisseria species reside in the same host niche, this may have important consequences for co-colonization or competition. Recent human challenge studies have demonstrated that commensals can impact nasopharyngeal carriage of pathogens (Deasy et al, 2015) and raise the possibility of using non-pathogenic Neisseria strains as 'bacterial medicine' (Deasy et al, 2015). An increased understanding of the molecular mechanisms underlying the association of specific isolates of commensal Neisseria with the human epithelium will not only improve our understanding of host-microbe interactions, but may also be informative for such approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological studies have shown an inverse relationship between carriage of N. lactamica and meningococci [1921]. It has been suggested that carriage of N. lactamica can inhibit meningococcal carriage [22, 23] and a recent study has shown that inoculation of N. lactamica in the oropharynx can both displace current carriage and protect against new acquisition of N. meningitidis [22]. …”
Section: Introductionmentioning
confidence: 99%